2018
DOI: 10.1016/j.cyto.2018.01.025
|View full text |Cite
|
Sign up to set email alerts
|

MERS-CoV infection in humans is associated with a pro-inflammatory Th1 and Th17 cytokine profile

Abstract: The Middle East respiratory syndrome coronavirus (MERS-CoV) has been recognized as a highly pathogenic virus to humans that infects the respiratory tract and is associated with high morbidity and mortality. Studies in animal models suggest that MERS-CoV infection induces a strong inflammatory response, which may be related to the severity of disease. Data showing the cytokine profiles in humans during the acute phase of MERS-CoV infection are limited. In this study, we have analyzed the profile of cytokine res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
493
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(541 citation statements)
references
References 65 publications
38
493
0
10
Order By: Relevance
“…22 MERS-CoV infection was also reported to induce increased concentrations of proinflammatory cytokines (IFNγ, TNFα, IL15, and IL17). 23 We noted that patients infected with 2019-nCoV also had high amounts of IL1B, IFNγ, IP10, and MCP1, probably leading to activated T-helper-1 (Th1) cell responses. Moreover, patients requiring ICU admission had higher concentrations of GCSF, IP10, MCP1, MIP1A, and TNFα than did those not requiring ICU admission, suggesting that the cytokine storm was associated with disease severity.…”
Section: (39%)mentioning
confidence: 94%
“…22 MERS-CoV infection was also reported to induce increased concentrations of proinflammatory cytokines (IFNγ, TNFα, IL15, and IL17). 23 We noted that patients infected with 2019-nCoV also had high amounts of IL1B, IFNγ, IP10, and MCP1, probably leading to activated T-helper-1 (Th1) cell responses. Moreover, patients requiring ICU admission had higher concentrations of GCSF, IP10, MCP1, MIP1A, and TNFα than did those not requiring ICU admission, suggesting that the cytokine storm was associated with disease severity.…”
Section: (39%)mentioning
confidence: 94%
“…The disease outcome, as well as the immunopathology and pathogenesis of MERS-CoV, SARS, and other respiratory viral infections in humans and other animals are strongly linked to the expression levels of inflammatory cytokines and chemokines [16,37,38]. Various cytokines, chemokines, and innate immune cells have been associated with the immunopathology during coronavirus (CoV) and influenza virus infection [5,6,13,14]. This study offers the first insight into the lung molecular gene expression profile of Th1 and Th2-related cytokines/ chemokines (Th1 & Th2 responses) during acute MERS-CoV infection.…”
Section: Discussionmentioning
confidence: 99%
“…According to the statistics provided by the World Health Organization (WHO) on June 10, 2019, a total of 2428 laboratory-confirmed cases of human MERS-CoV infection have been reported, with an estimated 838 deaths in 27 countries. The accumulated evidence suggested that MERS-CoV infections are characterized by high levels of systemic inflammatory cytokines/chemokines as well as immunopathology [4][5][6][7][8][9][10][11]. High inflammatory cytokines and chemokines levels have been strongly correlated with poor disease outcomes, immunopathology and massive infiltration of the immune inflammatory cells into the lungs [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…The plate was incubated at 37°C, in a 5% CO 2 incubator for 12 h. The supernatant was removed, and the Th1/Th2/Th17 cell-related cytokines IL-2, IFN-γ, TNF-α, IL-4, IL-6, IL-17A, and IL-10 were detected in accordance with the cytometric bead array kit instructions [21]. The Ms Th1/Th2/Th17 cytometric bead array kit was purchased from BD (USA).…”
Section: Methodsmentioning
confidence: 99%